EMOTIONAL INTELLIGENCE AND ITS RELATIONSHIP WITH PSYCHOLOGICAL LONELINESS AMONG PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER - Ali Al-Saree, Ihsan Igdifan; Alshurman, Wael Mohammad (European Scientific Journal, ESJ, 2015)
The aim of this present study is to identify the emotional intelligence and its relationship with loneliness among parents of children with autism in Jordan. The study sample totaling 100 families consisted of all the families of autistic children in Amman Governorate in Jordan. The researchers made use of two tools: Emotional Intelligence Scale, and the measure of psychological unity. The results indicated that the level of emotional intelligence of the parents of children with autism in Jordan was at an average. The psychiatric unit level had a very low level because the results showed that the correlation coefficient between emotional intelligence and the level of psychological unity was 0.006 with a level of significance of 0.933. However, this shows a lack of correlation between emotional intelligence and psychological unity.